Effect of offtake channel base angle of stepped spillway on scour hole - Tuna, M.C. (My University, 2012)
Scour holes formed downstream from a stepped spillway may affect the safety and stability of a structure. The development of such scour hole can cause failure of the structure by undermining the riverbed, thus it is important to develop criteria that result in understanding how such a scour hole can develop. The literature contains many studies dealing with energy dissipation, aeration and oxygen transfer in stepped spillways. However, their downstream scour hole depth and geometry is not well documented. In this study, a physical model is employed to study the impact of offtake channel base angle of stepped spillways on the scour hole. The area of the longitudinal profile of the scour hole is used to evaluate the amount of scour at downstream from the stepped spillways. Experimental results showed that the takeoff angle of 30° is the optimum angle which gives minimum longitudinal area and maximum depth of the scour hole. © Shiraz University.
Keywords: Offtake channel base angle; Scour depth; Scour hole geometry; Stepped spillway